Parametrization of Atmosphere-Surface exchange of CO2 over sea ice - Sørensen, Lise lotte; Jensen, Bjarne; Glud, Ronnie N.; McGinnis, Daniel; Sejr, Mikael Christian; Sievers, Jakob; Søgaard, Dorthe; Tison, Jean-Louis; Rysgaard, Soren (2014)
info:eu-repo/semantics/published